Crisis Management - Theory and Practice 2018
DOI: 10.5772/intechopen.74964
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance in Downturn Times: Detection and Alert – The New Italian Insolvency and Crisis Code

Abstract: In its life cycle, an enterprise may experience periods of crisis. If the crisis is monitored promptly and appropriate measures are taken, not only may the enterprise continue to operate but it may also be able to seize opportunities for growth. The Italian legislator is introducing a procedure aimed at supporting companies to detect the very first warning signs of a crisis. The supervisory board of auditors, the audit firm, and certain qualified creditors will have the right and duty to start the early warnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In order to protect stakeholders, the Board of Statutory Auditors manages an extensive system of controls related to, first of all, compliance with the reference standards for the preparation of financial statements and, second, compliance with the law and the Articles of Association [18]. Of particular importance is overseeing the timely implementation of mandatory requirements in the event of significant losses, such as to jeopardise business viability [19].…”
Section: The Role Of the Board Of Statutory Auditorsmentioning
confidence: 99%
“…In order to protect stakeholders, the Board of Statutory Auditors manages an extensive system of controls related to, first of all, compliance with the reference standards for the preparation of financial statements and, second, compliance with the law and the Articles of Association [18]. Of particular importance is overseeing the timely implementation of mandatory requirements in the event of significant losses, such as to jeopardise business viability [19].…”
Section: The Role Of the Board Of Statutory Auditorsmentioning
confidence: 99%
“…Top management and board must cooperate to focus on internal governance during a crisis to address potential damage. 5 Based on analysing crises situations, Riva et al (2018) note that corporate governance is particularly crucial in downturn times; otherwise, a firm might be affected miserably; and if the crisis is monitored promptly and appropriate measures are taken, not only the enterprise may continue to operate, but it may also be able to seize growth opportunities. It has been observed that in an institution with sound corporate governance practices, boards often play a crucial role in reinforcing the purpose of the organisation with management, reminding leaders of societal obligations, and making sure that, even in the depth of the crisis, the entity's response serves the heart of the organisation (Deloitte, 2020).…”
Section: Background Notementioning
confidence: 99%
“…The external and internal corporate supervisory bodies, i.e. the external auditors and the internal board of statutory auditors (collegio sindacale), have the obligation to verify that the board of directors ensures that the company has an adequate organisational structure, and a functioning system of internal controls, included a reliable and effective dashboard of indicators that monitors all the parameters and thresholds identified by the new law (Riva et al 2018). This should allow the directors to detect the early signals of a crisis, and the supervisory bodies to informally alert the directors of deficiencies in the managerial control system.…”
Section: The New Italian Framework For Crisis Managementmentioning
confidence: 99%
“…In case the out of court negotiations with the creditors, assisted by the professionals appointed by the Crisis settlement body for companies, are not successful, the crisis enters the stage of reversible insolvency. Italian bankruptcy law regulates this passage, with several court-assisted restructuring reorganisation procedures devised according to the principle that a debtor with a potentially profitable business should be given the opportunity to demonstrate that there is a greater benefit for the creditors in the long term in avoiding judicial liquidation (Riva et al 2018).…”
Section: The New Italian Framework For Crisis Managementmentioning
confidence: 99%
See 1 more Smart Citation